ISU-ISU INSTITUSIONAL DALAM PENERAPAN KURIKULUM MERDEKA PADA PEMBELAJARAN PAI DI SMA - Hazli, Muhammad Khairul; Amanda, Nadya Rizki; Fadriati, Fadriati; Suryana, Ermis (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This research aims to analyze the issues that arise in the implementation of the Independent Curriculum in Islamic Religious Education (PAI) learning in Senior High Schools (SMA). The Independent Curriculum, which is designed to encourage project-based learning and student character development, presents both opportunities and challenges for PAI teachers in managing diverse classes. Data was collected through in-depth interviews, classroom observations, and document analysis. The research results show that several main issues include difficulties in developing teaching modules that are in accordance with religious values, limited time in managing a busy curriculum, and the need for further training for teachers in implementing student-centered learning methods. In addition, lack of support from parents and challenges in assessing students' attitudinal competence are additional obstacles in achieving learning goals. This study recommends continued support from the government, increasing teacher capacity, and synergy with parents to optimize the implementation of the Merdeka Curriculum in PAI subjects. It is hoped that the results of this research can become a reference for developing a curriculum that is more adaptive and relevant to the needs of students.